Beef Marketing Analysis PT. Lembu Andalas Langkat Stabat - A. Setiawan; G. A. W. Siregar; E. Mirwandhono; K. C. Desnamrina; S.Mulatsi (Talenta Publisher, 2023)
Marketing is all the factors that are responsible for beef being distributed from the production location to where beef are consumed. This study aims to identify the characteristics of marketing institutions, big agents and retailers/small agents marketing beef, beef marketing channels, analyze marketing margins, farmer's share, beef marketing costs, and analyze beef marketing efficiency at PT Lembu Andalas, Langkat. This research was conducted in July 2022 â€“ August 2022. The sampling method chosen was snowball sampling, namely by following marketing channels from producers to consumers. Data was collected by using interview techniques using questionnaires. The results of this study indicate that there are two marketing channels. The smallest marketing margin is obtained in marketing channel II. The bigst farmer's share is obtained in marketing channel Â I. So it can be concluded that the first and second channels are efficient channels Â because they have an efficiency value of >1.